Severity of Stress in Acne Patients Attending Dermatology Outpatient Department of Tertiary Hospital in Kathmandu - Shrestha, Amrita; Pokhrel, Dinesh Binod; Parajuli, Sudip; Chapagain, Manisha; Shrestha, Rabina (Nepal Journal of Dermatology, Venereology & Leprology, 2021)
Introduction: Stress persists when a person is unable to cope with the situations of the past, present or future. Stress may be associated with physical and psychological abnormalities. Acne vulgaris is a chronic inflammatory disease of the pilo-sebaceous units with prevalence of more than 85% in adolescent age group. Materials and Methods: Three hundred one patients were recruited in the study. Inclusion criteria included new acne patients of age 16 years and above as well as those who were using but not improving with topical or oral acne therapies. Exclusion criteria included patients receiving sedatives, antidepressants, or glucocorticoids, patient suffering from chronic illnesses like diabetes, hypothyroidism, chronic kidney disease, migraine and other diseases. This questionnaire included biodata of the patients, clinical history and their perceived stress scale. Global Acne Grading System (GAGS) was used to assess acne severity in relation to stress using the Perceived Stress Scale (PSS). Results: The results indicated an increase in stress severity positively correlated with an increase in acne severity, which was statistically significant (p<0.01). Most of the patients were students. Subjects with higher stress scores, determined using the PSS, had higher acne severity when examined and graded using the GAGS. Conclusions: The results showed that there is a positive correlation between severity of stress and grade of acne. Stress management should be a part of acne management.